Durable and dendrite-free aqueous zinc battery and zinc-bromine flow battery
By using threshold-level electrolyte additives such as HPAA in aqueous zinc batteries to regulate zinc deposition, the problems of zinc dendrite growth and side reactions were solved, achieving high stability and long lifespan performance of zinc batteries.
Patent Information
- Application Number
- CN202410739964.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-07
- Publication Date
- 2025-12-09
AI Technical Summary
In slightly acidic aqueous electrolytes, zinc metal deposition is accompanied by the nucleation of zinc hydroxyl complexes and hydrogen evolution reactions, leading to electrolyte consumption and zinc dendrite growth, which affects the stability and lifespan of the battery.
Threshold-level electrolyte additives, such as hydroxyphosphonic acid-acetic acid (HPAA), are used to regulate zinc deposition and inhibit dendrite growth and side reactions by forming hydrogen bonds with the zinc surface and water molecules.
The zinc battery achieved no capacity loss in 250 cycles and stable operation for 180 to 365 days, while the zinc-bromine flow battery achieved no capacity loss in 800 cycles, significantly improving the battery's durability and stability.
Smart Images

Figure CN121097233A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates generally to the fields of materials science and electrochemistry. More specifically, the present invention relates to a threshold-level electrolyte additive for a durable aqueous zinc battery. BACKGROUND
[0002] With the growing demand for large-scale energy storage applications, rechargeable aqueous zinc-ion batteries are receiving increasing attention, especially considering the cost-effectiveness, intrinsic safety, low redox potential (-0.76 V vs. standard hydrogen electrode (SHE)), and competitive energy density (820 mAh g -1 ) of metallic zinc. However, the deposition of zinc metal in a slightly acidic aqueous electrolyte is usually accompanied by the nucleation of zinc hydroxyl complexes and the hydrogen evolution reaction (HER), which leads to the excessive consumption of electrolyte and the invasive growth of zinc dendrites, resulting in battery failure.
[0003] Various strategies from the geometric design of zinc anodes and separators to the electrolyte configuration have made progress in controlling zinc nucleation and growth as well as suppressing side reactions. For example, zinc-titanium alloys were found to be able to suppress intergranular corrosion and facilitate the uniform deposition of zinc anodes. However, the adverse effects of these anode treatment methods have not yet been addressed.
[0004] It was found that miscible molecules with higher Gutmann donor number (DN) than water (DN = 18), such as dimethyl sulfoxide (DMSO, DN = 29.8) and N,N-dimethylacetamide (DMA, DN = 27.8), can restructure the solvation sheath of Zn 2+ , thereby suppressing the reduction of water and the growth of zinc dendrites. However, the adverse effects of these anode treatment methods have not yet been fully addressed. For example, the overuse of water-soluble polar organic solvents can lead to the inevitable dissolution of classic conversion-type cathode materials such as halogens, chalcogens, and their derivatives, and the complex design of either the anode or the separator is not a particularly cost-effective choice; each solution can weaken the applicability of zinc anodes in a wider range.
[0005] Unlike the complete change of electrolyte and zinc surface, the additive engineering of aqueous electrolyte can be the most promising method to offset the degradation of zinc anodes and ensure their universal applicability in various aqueous zinc-ion batteries. The dosage of additives in aqueous electrolyte can be reduced to less than 1 millimole, which provides an economical and universally applicable method to regulate the deposition of zinc without worrying about the cathode part. However, the resulting battery reversibility is far lower than that of batteries treated by traditional methods, which highlights the importance of developing effective electrolyte additives while keeping a reasonably low dosage to consider economic factors. SUMMARY
[0006] Uncontrolled growth of zinc metal in mildly acidic aqueous electrolytes has severely hindered the development of zinc batteries. Moreover, practical strategies to combat the side reactions at the anode can instead degrade the economics of the battery and lead to degradation at the cathode end. This problem highlights the importance of electrolyte additive engineering that can introduce universal and compatible additives to regulate zinc flux and suppress dendrite growth.
[0007] Accordingly, in a first aspect, the present invention provides a durable and dendrite-free aqueous zinc battery comprising an anode, a cathode, an aqueous electrolyte comprising a threshold level electrolyte additive, and a separator. The threshold level electrolyte additive is capable of providing at least one hydrogen proton to form a hydrogen bond with an adjacent water molecule.
[0008] In an embodiment, the anode comprises zinc plate, zinc powder, or zinc foil.
[0009] In an embodiment, the cathode comprises a current collector, at least one active material, one or more electronically conductive particles, and at least one binder.
[0010] The current collector is selected from the group consisting of carbon cloth, carbon paper, graphite paper, titanium foil / net, and stainless steel compatible with the cathode.
[0011] The at least one active material comprises a halogen-based material or Zn x V2O5, MnO2, wherein x ranges from 0-0.25. The halogen-based material comprises a halogen, a halide, or a derivative thereof.
[0012] In an embodiment, the aqueous electrolyte comprises one or more zinc salts as solutes. The one or more zinc salts are selected from the group consisting of Zn(TFSI)2, Zn(OTF)2, Zn(PF6)2, Zn(ClO4)2, Zn(BF4)2, Zn(DFOB)2, ZnSO4, Zn(OAc)2, ZnCl2, ZnBr2, and ZnI2.
[0013] In an embodiment, the threshold level electrolyte additive comprises an organophosphorus compound having the following chemical formula (1):
[0014] In another embodiment, the threshold level electrolyte additive is selected from the group consisting of hydroxy phosphonic acid-acetic acid (HPAA), hydroxy ethylidene diphosphonic acid (HEDP), alendronic acid, and amino tris(methyl phosphonic acid).
[0015] In an embodiment, the aqueous electrolyte comprises the threshold level electrolyte additive in a feed amount of 5 to 10 ppm.
[0016] In one embodiment, the durable and dendrite-free aqueous zinc battery is capable of at least 250 cycles of operation without capacity loss.
[0017] In one embodiment, the durable and dendrite-free aqueous zinc battery is capable of a run period of up to 180 days to 365 days.
[0018] In one embodiment, the durable and dendrite-free aqueous zinc battery is capable of stable operation for 2000 hours at 5 mA cm-2, 2 mAh cm-2and stable operation for 500 hours at 10 mA cm-2, 10 mAh cm-2.
[0019] In a second aspect, the present application provides a durable and dendrite-free zinc-bromine flow battery comprising a cathode side comprising a catholyte, a current collector and a carbon felt; an anode side comprising an anolyte and the carbon felt; and a separator between the cathode side and the anode side.
[0020] The anolyte and the catholyte comprise a threshold level electrolyte additive in a feed amount ranging from 5 to 10 ppm, and the anolyte and the catholyte are flowed to a reaction cell by a peristaltic pump, and the zinc || bromine flow battery is capable of at least 800 cycles of operation without capacity loss.
[0021] In one embodiment, the catholyte comprises 2 mol L -1 zinc bromide and 0.4 mol L -1 1-ethyl-1-methylpyrrolidinium bromide, and the anolyte comprises 2 mol L -1 zinc bromide and 3 mol L -1 potassium chloride.
[0022] In one embodiment, the carbon felt has a geometric area of 4.0 cm 2 and a thickness of 1-5 millimeters.
[0023] Preferably, the carbon felt on the catholyte or the anolyte has a thickness of 2 millimeters.
[0024] In one embodiment, the reaction cell comprises polytetrafluoroethylene (PTFE) end plates, PTFE cavities, PTFE gaskets, PTFE spacers, PTFE tubes, carbon plates or titanium foils.
[0025] In one embodiment, the threshold level electrolyte additive comprises an organophosphorus compound having the following chemical formula (1):
[0026] In one embodiment, the threshold level electrolyte additive is selected from the group consisting of one or more zinc salts selected from the group consisting of hydroxy phosphonic acid-acetic acid (HPAA), hydroxy ethane diphosphonic acid (HEDP), alendronic acid, and amino tris(methyl phosphonic acid).
[0027] The present invention provides a highly convenient modification method that can inhibit dendrite growth and undesirable side reactions in aqueous (resting) zinc-ion batteries and zinc||bromine flow batteries. The sub-chemical additive is expected to reside on the zinc surface and interact with surrounding water molecules to regulate zinc deposition in these energy storage systems.
[0028] The improved electrolyte provides a model system that can be used to support the development of low-cost, high-performance, and durable aqueous zinc batteries for large-scale energy storage using deposition / stripping chemistry. Compared with the prior art, the preparation process is simple and economical, and the prepared product exhibits extremely significant effects and applicability in various zinc batteries.
[0029] Compared with the prior art, the present invention provides the following main advantages: (1) The ppm-level additive makes the electrolyte have a simple and clear preparation process; (2) The electrolyte additive engineering meets the requirements of low cost, low environmental pollution, and high compatibility with various energy storage systems; (3) The battery equipped with the improved electrolyte exhibits excellent long-term running performance (up to nearly one year for zinc symmetric batteries), which is due to optimized zinc flux and reduced zinc dendrites; (4) The present invention proposes a highly compatible strategy that can achieve highly stable zinc chemistry without being hindered by cathode chemistry. BRIEF DESCRIPTION OF DRAWINGS
[0030] Embodiments of the present invention are described in more detail below with reference to the drawings, in which:
[0031] Figure 1A The interaction between hydroxy phosphonic acid acetic acid (HPAA) and water is shown. The inset shows the electrostatic potential map of HPAA. Figure 1B The intramolecular coordination between HPAA and water and the corresponding bond energies (numbers 1-10) are shown; and the intermolecular coordination of water (number 11). Figure 1C The Fourier transform infrared spectra of ZnSO4 electrolyte containing different amounts of HPAA are shown. Figure 1D The 1H NMR spectra of ZnSO4 electrolyte and electrolyte containing 5 ppm HPAA are shown.
[0032] Figure 2AAdsorption of HPAA on the (101) and (002) lattice planes of zinc surface is shown, and the electrostatic potential is mapped by the electron density surface. Figure 2B Molecular dynamics simulation of HPAA is shown, Figure 2C The corresponding energy evolution is shown.
[0033] Figure 3 X-ray diffraction (XRD) patterns of zinc metal treated with the studied electrolytes are shown.
[0034] Figure 4A The design of the zinc surface functionalization with HPAA is shown. Figure 4B X-ray diffraction patterns of the treated zinc metal are shown. Figure 4C The X-ray diffraction patterns are shown in a wider field of view. Figure 4B The X-ray diffraction patterns are shown in a wider field of view.
[0035] Figure 5A The crystal size of zinc hydroxyl complex is shown. Figure 5B Scanning electron microscope (SEM) images of the treated zinc metal are shown. Figure 5C O 1s core electron spectroscopy (XPS) plots of fresh zinc metal and zinc metal after 10 minutes of treatment are shown. Figure 5D Zn 2p XPS plots of fresh zinc metal and zinc metal after 10 minutes of treatment are shown.
[0036] Figure 6A The P 2p core electron spectroscopy plots of zinc anode before and after HPAA treatment are shown. Figure 4A The P 2p core electron spectroscopy plots of zinc anode before and after HPAA treatment are shown. Figure 6B The interaction between HPAA and zinc hydroxide is shown.
[0037] Figure 7A The HOMO-LUMO structure and energy level diagram of HPAA are shown. Figure 7B Linear sweep voltammetry (LSV) plots of Zn||ZnS04||Ti and Zn||ZnS04 / HPAA||Ti cells are shown. Figure 7C Linear polarization plots of Zn||ZnS04||Ti and Zn||ZnS04 / HPAA||Ti cells are shown. Figure 7D CA curves of Zn||ZnS04||Ti and Zn||ZnS04 / HPAA||Ti cells are shown.
[0038] Figure 8A 3D snapshots of 2M ZnS04and 1.3 wt% HPAA in 2M ZnS04in MD simulation, and partially magnified snapshots, representing the structure of the electrolyte, are shown. Figure 8B RDF of Zn 2+ -O(H20) is shown. Figure 8CMean square displacement (MSD) of Zn 2+ and water in the electrolyte under study. Figure 8D CV curves of Zn||ZnS04||Ti and Zn||ZnS04 / HPAA||Ti cells are shown. Figure 8E Evolution of the charge during each stripping and plating step is shown.
[0039] Figure 9A XRD patterns of the zinc electrode of the Zn||Zn cell during stripping / plating are shown, Figure 9B Correlated SEM images of the plating face are shown. Figure 9C SEM images of the cycled Zn||ZnS04||Zn and Zn||ZnS04 / HPAA||Zn are shown. “P” and “S” indicate respectively the last cycle is plating zinc and stripping zinc. Figure 9D SEM images and SEM mapping of the plating face of Zn||ZnS04||Zn and Zn||ZnS04 / HPAA||Zn are shown.
[0040] Figure 10A Zn||Zn cells cycled at 1 mA cm -2 , 1 mAh cm -2 are shown. Figure 10B Zn||Zn cells cycled at 10 mA cm -2 , 1 mAh cm -2 are shown.
[0041] Figure 11A Zn||ZnS04||Zn and Zn||ZnS04 / HPAA||Zn cells at varying current densities are shown. Figure 11B Zn||ZnS04||Zn and Zn||ZnS04 / HPAA||Zn cells cycled at 5 mA cm -2 , 2 mAh cm -2 are shown, and Figure 11C The corresponding zoom curves for specific ranges are shown. Figure 11D Zn||ZnS04||Zn and Zn||ZnS04 / HPAA||Zn cells cycled at 10 mA cm -2 , 10 mAh cm -2 are shown, and Figure 11E The corresponding zoom curves for specific ranges are shown.
[0042] Figure 12A Zn||Cu cells cycled at 1 mA cm -2 , 1 mAh cm -2 are shown. Figure 12B Zn||Cu cells cycled at 1 mA cm-2 1mAh cm -2 Selected charge-discharge curves for a Zn||ZnSO4||Cu asymmetric cell undergoing cycling.
[0043] Figure 13 The structure of a laboratory-scale Ah-level Zn||ZnSO4 / HPAA||ZnVO pouch cell is shown.
[0044] Figure 14A This shows Zn||Zn based on ZnSO4 or ZnSO4 / HPAA. 0.25 CV curves of a full V2O5 cell. Figure 14B This shows Zn||Zn based on ZnSO4 or ZnSO4 / HPAA. 0.25 DRT spectrum of V2O5 full cell. Figure 14C This shows Zn||Zn based on ZnSO4 or ZnSO4 / HPAA. 0.25 EIS spectrum of V2O5 battery.
[0045] Figure 15A This shows the Ah level of Zn||ZnSO4 / HPAA||Zn 0.25 Photo of a V2O5·nH2O pouch cell. Figure 15B Describes Ah-level Zn||ZnSO4 / HPAA||Zn 0.25 Long-term cycle performance of V2O5·nH2O pouch cells. The inset shows representative voltage curves of the pouch cells. Figure 15C Displays Zn at Ah level ||ZnSO4 / HPAA ||Zn 0.25 Selected GCD curves for V2O5·nH2O pouch cells.
[0046] Figure 16A A schematic diagram of the reversible fluorescent flow cell under study is shown. Figure 16B It shows 40mA cm -2 20mAh cm -2 Cyclic Zn||CF flow cell, and Figure 16C The corresponding voltage is shown as it evolves over time. Figure 16D The long-term cyclic coulombic efficiency of the Zn||Br2 reversible fluorescent current cell is shown at different current densities. Figure 16E Show the GCD curves of Zn||Br2 flow cells with and without HPAA. Figure 16F The coulombic efficiency of the Zn||Br2 reversible fluorescent current cell is shown at different current densities. Detailed Implementation
[0047] Zinc-ion batteries show potential prospects for future energy storage, but dendrite growth, hydrogen evolution reaction (HER), and local deposition, etc. seriously hinder their development in practical applications.
[0048] Therefore, the present application provides a durable and dendrite-free aqueous zinc battery comprising a cathode, an anode, an aqueous electrolyte containing a threshold level electrolyte additive, and a separator. Unlike complex structural design and electrolyte concept, the present application proposes a threshold level electrolyte additive to overcome the inherent problems of zinc anode in mild acidic aqueous electrolyte. The present application creates a new record in its feed amount (5 ppm), cumulative capacity (84.19 Ah cm-2) and current density (10 mA cm-2), significantly surpassing the existing aqueous zinc batteries.
[0049] In one embodiment, the aqueous electrolyte comprises a zinc salt as a solute. The zinc salt can comprise Zn(TFSI)2, Zn(OTF)2, Zn(PF6)2, Zn(ClO4)2, Zn(BF4)2, Zn(DFOB)2, ZnSO4, Zn(OAc)2, ZnCl2, ZnBr2, and ZnI2.
[0050] In one embodiment, the threshold level electrolyte additive comprises an organophosphorus compound having the following chemical formula (1):
[0051] In another embodiment, the threshold level electrolyte additive comprises hydroxy phosphonic acid-acetic acid (HPAA), hydroxy ethylidene diphosphonic acid (HEDP), alendronic acid, and amino tris(methyl phosphonic acid).
[0052] Specifically, HPAA is a chemically stable organophosphorus compound characterized by one carboxyl group, one phosphonic hydroxyl group, and one hydroxyl group covalently bonded to one carbon atom, as shown in Figure 1A HPAA tends to adhere to the zinc metal surface and interact with surrounding water molecules to control zinc deposition. In addition, it helps to prevent unnecessary side reactions and remove impurities from the zinc surface.
[0053] DFT calculations reveal that the outer hydrogen atom part of HPAA is charged because oxygen atoms are more electronegative than carbon or hydrogen. This molecular geometry gives HPAA the characteristic of a high tendency to form hydrogen bonds with adjacent water molecules, which provides one hydrogen proton (-OH…OH2) with an average high binding energy of -0.76 eV; while for the -O…H2O hydrogen bond, its binding energy drops to -0.27 eV, close to the strength of the intermolecular hydrogen bond in water Figure 1B ).
[0054] In one embodiment, the feed amount of HPAA is in the range of 1-10 ppm. For example, approximately 5 ppm of HPAA is added to the electrolyte at room temperature. The low feed amount is effectively adsorbed on the zinc surface and optimizes zinc deposition, mitigating the adverse effects of HER and dendrite growth, thus the treated Zn||Zn symmetric cell can sustain a long period of operation of nearly one year.
[0055] In one embodiment, the use of HPAA enables Zn||ZnS04 / HPAA||Zn symmetric cell to operate at 1 mA cm -2 , 1 mAh cm -2 , and 10 mA cm -2 , 1 mAh cm -2 for up to 180 days to 365 days of cycling. Benefiting from the beneficial effect between HPAA adsorbed on the zinc surface and hydrogen bonding with adjacent water molecules, highly stable symmetric stripping / plating zinc in aqueous electrolyte (e.g. ZnS04electrolyte) can be achieved at 1 mA cm -2 , 1 mAh cm -2 , and 10 mA cm -2 , 1 mAh cm -2 for up to 362 days and 350 days of cycling, respectively.
[0056] As a proof of concept, the effectiveness of the threshold-level electrolyte additive was evaluated using Ah-level Zn||Zn 0.25 V205-nH20 (n = 0-0.5) pouch cells, which did not show any capacity loss over at least 250 cycles.
[0057] In one aspect, the present invention provides a durable and dendrite-free zinc-bromine flow battery, which includes a cathode side, an anode side, a catholyte and an anolyte containing a threshold-level electrolyte additive, and a separator. Larger scale Zn-Br2reversible fluorescent flow battery systems also show the benefits of the threshold-level electrolyte additive of the present invention. This battery can sustain at least 800 cycles without any capacity loss. Benefiting from the suppression of dendrite growth and side effects, a long-term operation of over 800 hours is achieved at 40 mA cm -2 with a higher coulombic efficiency.
[0058] Example
[0059] Example 1 - Materials and Methods
[0060] Chemicals and Reagents
[0061] Zinc bromide (99%), zinc sulfate (AR grade), hydroxyphosphonic acid acetic acid (HPAA, 50% solution), vanadium pentoxide (V2O5, 99%), zinc acetate (99.99%), zinc bromide (ZnBr2, 99%), zinc chloride (ZnCl2, 98%), 1-ethyl-1-methylpyrrolidinium bromide (MEP, 99%), and 1-methyl-2-pyrrolidinone (99%) were all purchased from Aladdin. Polyvinylidene fluoride (PVDF) and Ketjen black EC-300J were purchased from SOLVAY (Solef 1008) and Nouryon, respectively. All chemicals were used as received without further treatment.
[0062] Materials and Electrochemical Characterization
[0063] Zn 0.25 V2O5was prepared by dissolving 4 mmol of V2O5and 2.6 mmol of zinc acetate in a mixture of water and acetic acid (94:6% v / v) and then transferred to a sealed polytetrafluoroethylene container and heated at 200 °C for 72 h. The obtained precipitate was washed with water and acetone and dried at 60 °C for further use.
[0064] Fourier transform infrared (FTIR) measurements were performed using a Perkin Elmer FT-IR spectrometer. Powder X-ray diffraction (XRD) patterns were measured using a Rigaku Smartlab X-ray diffractometer with Cu Kα radiation X-ray photoelectron spectroscopy (XPS) analysis was performed on a PHI 5802 X-ray photoelectron spectrometer; the carbon spectrum (284.8 eV) was used as a reference for calibration. The morphology and elemental composition of the samples were studied using a FEI Quanta 250 scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS). Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests were performed on an electrochemical workstation (CHI 660E). The long-term stability and rate performance of the batteries were obtained at room temperature using a LAND battery test system.
[0065] Theoretical Calculations
[0066] First-principle calculations were performed based on density functional theory (DFT) using the Dmol3 module in the numerical atomic-centered basis function framework, and the Perdew-Burke-Ernzerhof (PBE) exchange-correlation functional form and generalized gradient approximation (GGA) were used to describe the exchange-correlation interaction of electrons. Gaussian double-ζ plus polarization numerical (DNP) basis sets were used to describe the valence electrons, while DFT semi-core pseudopotentials were used to describe the core electrons. The adsorption energy E ads was calculated by the following equation: E ads =E ensemble -E absorbent -E adsorbate Among them, E ensemble E represents the adsorbent. absorbent E represents the adsorbate. adsorbate This represents the energy of the entire system after adsorption.
[0067] Example 2 - Characterization of Prepared ZnS04Electrolyte
[0068] Figure 1C FTIR spectroscopy confirmed the strong interaction between HPAA and water in the 2M ZnSO4 electrolyte. Specifically, with increasing HPAA additive (0-10 ppm), the OH stretching vibration experienced a change from 3182 cm⁻¹ to 3182 cm⁻¹. -1 up to 3243cm -1 The continuous blue shift is due to the decrease in water molecule mass and the decrease in OH bond length, both of which suggest the breaking of hydrogen bonds between water molecules. Figure 1D Proton nuclear magnetic resonance (¹H NMR) measurements showed that the chemical shift shifted upward with the addition of HPAA (5 ppm), due to the increase in electron density and the decrease in the number of deshielded protons, indicating that the active protons in HPAA can affect the inherent water hydrogen bond network by constructing new -OH…OH2 bond structures.
[0069] from Figure 2A It can be seen that although the role of HPAA is no longer limited to hydrogen bond acceptor, the electronegative oxygen atoms in HPAA play an important role in the adsorption on the zinc surface, especially along the (002) crystal plane of zinc, resulting in a significant binding energy of -0.73 eV.
[0070] The adsorption capacity of HPAA was further confirmed by molecular dynamics (MD) simulations. Figures 2B-2C As shown, HPAA suspended in ZnSO4 electrolyte successfully reaches the zinc electrode at 240 ps and moves along the surface edge over the next 3760 ps, contributing to an overall decrease in system energy and thus making the system more stable. The formation of basic zinc sulfate is minimized due to local pH increases and the concurrent HER, resulting from unadjusted water clusters and the dynamic adsorption of HPAA on the zinc surface.
[0071] like Figure 3As shown, zinc metal immersed in ZnSO4 electrolyte for 10 days exhibited strong XRD diffraction from basic zinc sulfate 3Zn(OH)2·ZnSO4·5H2O, abbreviated as Zn4SO4(OH)6·5H2O. Notably, the crystallization process was significantly suppressed by introducing 1 ppm HPAA into the ZnSO4 electrolyte; when the addition reached 5 ppm, the crystal signal completely disappeared.
[0072] Subsequently, a further anodic treatment strategy achieved sub-ppm level adsorption on the zinc surface ( Figure 4A Specifically, zinc metal was immersed in a mixed solution of 0.1 wt.% HPAA and ZnSO4 electrolyte for 0, 1, 5 or 10 minutes, followed by rinsing with water and then immersion in ZnSO4 electrolyte for ten days.
[0073] like Figures 4B-4C As shown, the XRD results indicate that the crystallinity of basic zinc sulfate gradually decreases with the extension of treatment time, and its hydration number decreases from 5 (3Zn(OH)2·ZnSO4·5H2O) to 4 (3Zn(OH)2·ZnSO4·4H2O) and 3 (3Zn(OH)2·ZnSO4·3H2O), accompanied by a gradually weakening crystallization peak, indicating that it has the ability to inhibit the nucleation and growth of basic zinc sulfate.
[0074] like Figure 5A As shown, after HPAA treatment, the average grain size of the composite decreased to the nanoscale (<70 nm). Notably, the average size of the surface zinc also decreased slightly, which may be attributed to the improved surface morphology of HPAA. [Continue to...] Figure 5B SEM images further supported the crystallization evolution of basic zinc sulfate. In the control sample, a large number of insulating bulk crystals accumulated on the zinc surface, while these crystals disappeared after treatment in the suggested mixed solution for 10 minutes. Following treatment, according to... Figures 5C-5D In high-resolution X-ray photoelectron spectroscopy, the bonding between oxides and zinc metal becomes weaker, while the bonding between zinc metals is enhanced.
[0075] Soak for 10 minutes ( Figure 6A The slight signal appearing in the P2p region may indicate the adsorption of HPAA on the zinc surface. Notably, the control sample's Zn2p core energy spectrum exhibits a unique broad peak, which is due to the accumulation of valence charge near zinc, favoring the nucleation of basic zinc sulfate. Figure 6B The DFT results strongly demonstrate that after HPAA adsorbs on the Zn(OH)2 surface, the energy decreases significantly at multiple contact angles, which helps to inhibit the nucleation and growth of hydroxides.
[0076] Example 3 - Electrochemical Impact of HPAA
[0077] To passivate the zinc surface and tune the hydrogen bond network in water, ZnS04electrolyte with 5 ppm HPAA additive was further introduced for electrochemical studies.
[0078] The lower HOMO energy level of HPAA molecule is theoretically beneficial for stronger attraction of free electrons, thus increasing the energy barrier for HER Figure 7A ). Figure 7B The experimental results in the inset show that a vigorous HER reaction occurs in the three-electrode Zn||ZnS04||Ti cell. Remarkably, upon addition of HPAA, the HER is significantly suppressed in the ZnS04electrolyte with 5 ppm HPAA, as evidenced by the decrease in current and disappearance of hydrogen bubbles, accompanied by a substantial reduction in corrosion current, indicating more uniform zinc deposition Figure 7C ). As shown in the inset, chronoamperometry (CA) measurements reveal a lower reduction current and fast three-dimensional diffusion process in the ZnS04electrolyte with 5 ppm HPAA due to the absence of a significant HER reaction. Figure 7D
[0079] Figures 8A to 8C Molecular dynamics simulations in the inset further demonstrate that in the ZnS04electrolyte with 5 ppm HPAA, the zinc flux is guided (to some extent, promoting uniform deposition) and is beneficial for the desolvation of Zn 2+ cations near the zinc electrode. Therefore, highly reversible CV curves were achieved in the Zn||ZnS04 / HPAA||Ti system at a scan rate of 1 mV s -1 , accompanied by a low and stable deposition current Figure 8D ). The evolution of CV curves is visible in the inset, where the charge / discharge capacity and the associated nucleation potential of the Zn||ZnS04 / HPAA||Ti system mostly remain stable, which is attributed to the highly reversible zinc stripping / plating process. Figure 8E
[0080] Example 4 - Static Cell Assembly
[0081] A Zn||Zn symmetric button cell was assembled using two 100-micrometer-thick zinc foils with a layer of glass fiber separator (Whatman, GF / C) in between and adding 2 mol / L ZnS04electrolyte with additional 5 ppm HPAA. The Zn||ZnVO button cell was prepared in a similar manner, where the cathode was Zn 0.25 V2O5material prepared by mixing Zn 0.25 V₂O₅, Ketjen Black, and PVDF were mixed in a mass ratio of 7:2:1, coated onto the surface of conductive carbon cloth, and dried in a vacuum oven at 80°C. Subsequently, the cathode electrode was cut to a 1×1 cm area, symmetrically positioned with a zinc sheet of the same size, and sandwiched between a membrane moistened with ZnSO₄ electrolyte to prepare a button cell.
[0082] At 1mA / cm 2 1mAh / cm 2 Under certain conditions, a ZnSO4 electrolyte containing 5 ppm HPAA provided more symmetrical and reversible deposition in Zn||Zn cells, and after 300 cycles, its f D The value is 4.4%. Under the same conditions, the Zn||ZnSO4||Zn battery, after 50 cycles, shows a decrease in fi due to the large accumulation of zinc hydroxide complexes. D The value almost tripled, which is a sign of HER. Figure 9A ).
[0083] Figure 9B The superimposed SEM images show that the galvanized electrode surface is smooth and clean, while the control sample is mainly dominated by hydroxyl byproducts and deep cracks. Figure 9C and 9D In the SEM images and SEM-mapping images, a wider field of view was observed, further confirming the uniform deposition / stripping of zinc in the Zn||ZnSO4 / HPAA||Zn battery, without byproducts or corrosion spots.
[0084] Notably, after adding a ZnSO4 electrolyte containing 5 ppm HPAA, the Zn||Zn symmetric cells achieved a performance of 1 mA / cm². 2 1mAh / cm 2 and 10mA / cm 2 1mAh / cm 2 Under these conditions, it can operate sustainably for 362 days and 350 days. In contrast, the control group Zn||ZnSO4||Zn battery completed its operation in just 120 hours. Figures 10A-10B HPAA's excellent performance primarily stems from its passivation effect on zinc surfaces and its interaction with water molecules. Particularly noteworthy is its performance in the early cycling stages, such as... Figure 10A As shown, the Zn||ZnSO4 / HPAA||Zn battery underwent an optimization process involving in-situ exfoliation, thus confirming the modification of the zinc surface by HPAA, which is consistent with... Figure 5A The reduction in zinc grain size shown is consistent with this.
[0085] refer to Figure 11A HPAA induces Zn||Zn symmetric cells to operate at different current densities (from 0.5 mA / cm²). -2up to 10mAcm -2 Successful cycling was achieved, effectively preventing short circuits. This specialized technology was subsequently developed to enable long-term cycling at higher current densities and areal capacities. Specifically, in ZnSO4 electrolyte, the battery may fail due to zinc dendrite penetration (leading to short circuits) or channel blockage. However, in the Zn||ZnSO4 / HPAA||Zn battery, it achieves this at 5 mAcm -2 2mAh cm -2 It operated stably for 2000 hours under these conditions, at 10mA cm -2 10mAh cm -2 It operated stably for 500 hours under certain conditions. Figures 11B-11E ).
[0086] Figure 12A The reversibility of zinc deposition was further verified by the Zn||ZnSO4 / HPAA||Cu configuration. At 1 mA cm⁻¹ -2 1mAh cm -2 Under these conditions, the configuration successfully completed 1000 cycles (2000 hours) with an average coulombic efficiency (CE) of 99.2%. In contrast, the Zn||ZnSO4||Cu configuration experienced membrane perforation after 100 cycles, leading to a short circuit in the battery. Figure 12B ).
[0087] Example 5 - Assembly of Ah-rated Zn||Zn 0.25 V2O5.nH2O (n = 0 - 0.25) pouch cells
[0088] To evaluate the capabilities of HPAA in practical applications, Figure 13 The diagram shows Zn||ZnSO4 / HPAA||Zn 0.25 V₂O₅·nH₂O full cell. Zn 0.25 The assembly of a V₂O₅ pouch cell is essentially an enlarged version of a button cell. Specifically, the cathode uses Zn. 0.25 V2O5 material, prepared by adding Zn 0.25 V₂O₅, Ketjen Black, and PVDF were mixed evenly in a mass ratio of 7:2:1, coated onto the surface of a titanium mesh, and dried in a vacuum oven at 80°C. Zn 0.25 V2O5 cathode (approximately 60 mg / cm³) -2Both the zinc anode and the diaphragm are shaped to 10 cm × 10 cm and packaged together with a slightly larger separator (10.4 cm × 10.4 cm) and an appropriate amount of ZnSO4 electrolyte (containing HPAA additive) in an aluminum foil bag. The bags are then sealed using an automated vacuum sealing machine from Wuhan Geruisi New Energy Co., Ltd. The assembled pouch cells are left to stand for 10 hours and then cycled 5 times at 1x current density to fully wet the thick electrodes. Hydrogen gas generated by the corrosion reaction is released by opening the packaging film, followed by resealing for formal testing.
[0089] according to Figure 14A From the cyclic voltammetry curves, it can be concluded that, apart from a slight contribution to the total charge, HPAA has a significant impact on Zn. 0.25 The V₂O₅·nH₂O cathode is inert. (Refer to...) Figure 14B ,Zn||Zn 0.25 The relaxation time distribution (DRT) curves of the V₂O₅·nH₂O full cell revealed three significant local maxima, all of which contributed to the total polarization resistance of the cell. DRT analysis was performed using the open-source MATLAB scripting software DRTtools to quantitatively deconvolve the EIS spectra. Figure 14C Anode (R) c1 ) and cathode (R ct2 The charge transfer resistance of Zn||ZnSO4 / HPAA||Zn differs only slightly in both cases, except that Zn||ZnSO4 / HPAA||Zn 0.25 Apart from a slight decrease in the polarization of V2O5·nH2O, this indicates that HPAA has no significant negative impact on this particular energy storage system.
[0090] To further test the effectiveness of HPAA, a 10 cm × 10 cm pouch cell was assembled and loaded with a large amount of Zn. 0.25 V2O5·nH2O (approximately 50mg cm) -2 ()( Figure 15A ).
[0091] Figure 15B Long-term cycling performance and Figure 15C The galvanostatic charge-discharge (GCD) curves in the figure verified that Zn||ZnSO4 / HPAA||Zn 0.25 Cycle stability of V2O5·nH2O pouch cells. Pouch cells at 200 mA g... -1 After 250 cycles at a current density, the battery maintains Ah-level capacity with high efficiency and negligible capacity loss. Despite the addition of a small amount of V₂O₅ to the electrolyte to compensate for the dissolution of the cathode material, the battery's cycle stability remains excellent.
[0092] Example 6 - Assembly of Zinc-Based Flow Batteries
[0093] To further validate the effectiveness and applicability of HPAA, the aqueous zinc-based redox flow batteries were studied, focusing on controlling zinc ion flux in a more extensive system. The zinc-based flow battery was assembled by sandwiching a porous polyolefin membrane (Daramic) between two carbon felt (CF) electrodes and clamped by two graphite plates. The effective area of the electrode was 2 x 2 cm2. The anolyte contained 2 mol L -1 of ZnBr2and 3 mol L -1 of KCl. For the battery containing HPAA, 20 ppm of HPAA was added to the anolyte. To slow down the diffusion of corrosive bromine, a bromine complexing agent was added to the catholyte. Here, 0.4 mol L -1 of MEP was added. These different anolyte and catholyte were used to flow through the battery.
[0094] Figure 16A A general configuration of zinc || Br2flow battery was demonstrated, including a current collector, a carbon felt electrode (2 x 2 cm 2 ), and a membrane in between, external anolyte / catholyte tanks were circulated by pumps to push the redox reactions.
[0095] Example 7 - Performance of Zinc-Based Flow Batteries
[0096] The batteries were operated at a constant current density, and the charging process was controlled by a specified capacity. The discharging process ended at a cutoff voltage of 0.8 V. The assembly method of Zn || CF flow battery was the same as that of Zn || Br2flow battery, with the only difference being that the cathode used a zinc plate connected to the carbon felt. The anolyte and catholyte were the same, both containing 2 mol L -1 of ZnBr2and 3 mol L -1 of KCl. All battery performance tests were performed by CT3001A, LAND battery test system.
[0097] At 40 mA cm -2 , 20 mAh cm -2 , the HPAA additive (10 ppm) enabled the Zn || CF flow battery to complete 500 reversible cycles (close to 100% CE), while the control sample almost failed to operate properly after 50 cycles Figure 16B . Due to the increasing deposition voltage on the CF over time, an irreversible Zn / Zn 2+ redox reaction was observed in the control sample, resulting in the corresponding voltage profile Figure 16C). The stable long-term cycling performance of the Zn || Br2 flow cell highlights the importance of the HPAA additive, which enables approximately 800 cycles at 40 mA cm -2 with near 100% CE Figure 16D ) consistently. In contrast, the same setup lacking HPAA exhibits gradually diminishing capacity and CE after 50 cycles, while also suffering from persistent dendrite growth and side reactions, leading to shorting and polarization, respectively Figure 16E ) as shown in the inset plot. The voltage profiles highlight the effect of adding the HPAA additive to the flow cell, which maintains good discharge capacity and minimizes charge-discharge polarization, as shown in Figure 16D . The rate performance summary shown in Figure 16F further demonstrates that HPAA promotes high and stable closure efficiency with little capacity decay even at high current densities up to 100 mA cm -2 .
[0098] The foregoing description of the application has been presented for the purposes of illustration and description. It is not intended to be exhaustive or to limit the application to the precise form disclosed. Many modifications and variations are possible in light of this disclosure.
[0099] The embodiments were chosen and described in order to best explain the principles of the application and its practical application, thereby enabling others skilled in the art to best utilize the application in various embodiments and with various modifications as are suited to the particular use contemplated.
[0100] Definitions
[0101] Throughout this specification, unless the context requires otherwise, the word "comprise", or variations such as "comprises" or "comprising" will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers. It will also be noted that, in this disclosure and particularly in the claims and / or paragraphs, terms such as "comprises", "comprised", "comprising" and the like can have the meaning ascribed to them in U.S. patent law; e.g., they can mean including, but not limited to, as set forth in U.S. Patent Law and practice.
[0102] Also, throughout this specification and claims, unless the context dictates the contrary, the word "comprise," or variations such as "comprises" or "comprising" will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers.
[0103] Reference throughout this specification to "one embodiment," "an embodiment," "exemplary embodiment," or similar terms means that a described embodiment can include a particular feature, structure, or characteristic, but every embodiment can not necessarily include the particular feature, structure, or characteristic. Furthermore, similarly described embodiments can not necessarily be mutually exclusive from one another.
[0104] As used herein and unless otherwise defined, the terms "substantially," "essentially," "approximately," and "about" are used to describe and account for small variations in, e.g., measurements, temperatures, etc. When used in conjunction with an event or circumstance, the terms can cover occurrences that deviate from the event or circumstance by a margin of a degree or amount that is minor in the context of the event or circumstance. For example, when used in conjunction with a numerical value, the terms can cover a range of variations less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%.
[0105] Other definitions for selected terms used herein can be found in the DETAILED DESCRIPTION of the Invention section and apply throughout. Unless otherwise defined, all other technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the application belongs.
[0106] Those skilled in the art will appreciate that, in view of these teachings, alternatives can be practiced without undue experimentation or deviating from the spirit or scope of the application as set forth in the appended claims. The application is merely limited by the appended claims, which include all such alternatives and modifications when viewed in light of the above specification and accompanying drawings.
Claims
1. A durable and dendrite-free aqueous zinc battery, characterized in that, The durable and dendrite-free aqueous zinc battery includes: One anode; A cathode; An aqueous electrolyte; Threshold-level electrolyte additives in the aqueous electrolyte, wherein the threshold-level electrolyte The additive can form a hydrogen bond with an adjacent water molecule by providing at least one hydrogen proton; as well as A diaphragm between the anode and the cathode, The durable and dendrite-free aqueous zinc battery described therein can operate for up to 180 to 365 days.
2. The durable and dendrite-free aqueous zinc battery of claim 1, wherein the anode comprises a zinc plate, zinc powder or zinc foil; and the cathode comprises a current collector, at least one active material, one or more conductive particles and at least one binder.
3. The durable and dendrite-free aqueous zinc battery of claim 2, wherein the current collector is selected from the group consisting of: carbon cloth, carbon paper, graphite paper, titanium foil / mesh, and stainless steel, which are compatible with the cathode.
4. The durable and dendrite-free aqueous zinc battery of claim 2, wherein the at least one active material comprises a halogen-based material or Zn x V2O5 and MnO2, where x ranges from 0 to 0.
25.
5. The durable and dendrite-free aqueous zinc battery of claim 1, wherein the aqueous electrolyte comprises one or more zinc salts as solutes.
6. The durable and dendrite-free aqueous zinc battery of claim 5, wherein the one or more zinc salts are selected from the group consisting of: Zn(TFSI)2, Zn(OTF)2, Zn(PF6)2, Zn(ClO4)2, Zn(BF4)2, Zn(DFOB)2, ZnSO4, Zn(OAc)2, ZnCl2, ZnBr2, and ZnI2.
7. The durable and dendrite-free aqueous zinc battery of claim 1, wherein the threshold-level electrolyte additive comprises an organophosphorus compound having the following chemical formula (1):
8. The durable and dendrite-free aqueous zinc battery of claim 7, wherein the threshold electrolyte is selected from the group consisting of: hydroxyphosphonic acid-acetic acid (HPAA), acetic acid monohydrate (HEDP), alendronate, and aminotris(methylphosphonic acid).
9. The durable and dendrite-free aqueous zinc battery of claim 1, wherein the aqueous electrolyte comprises the threshold-level electrolyte additive in a feed amount of 5 to 10 ppm.
10. The durable and dendrite-free aqueous zinc battery of claim 1, wherein the durable and dendrite-free aqueous zinc battery is capable of performing at least 250 cycles without capacity loss.
11. The durable and dendrite-free aqueous zinc battery of claim 1, wherein the durable and dendrite-free aqueous zinc battery is capable of stable operation for 2000 hours at 5 mA cm⁻² and 2 mAh cm⁻², and stable operation for 500 hours at 10 mA cm⁻² and 10 mAh cm⁻².
12. A durable and dendrite-free zinc-bromine flow battery, characterized in that, The durable and dendrite-free zinc-bromine flow battery includes: One cathode side includes catholyte, a current collector, and a carbon felt; One anode side includes anolyte and the carbon felt; as well as A diaphragm is located between the cathode side and the anode side. The anolyte and the catholyte include a threshold-level electrolyte additive in a feed range of 5 to 10 ppm. The anolyte and the catholyte flow to the reaction tank are pumped by a peristaltic pump, and the zinc||bromine flow battery is capable of performing at least 800 cycles without capacity loss.
13. The durable and dendrite-free zinc-bromine flow battery of claim 12, wherein the cathode fluid comprises 2 mol L⁻¹ zinc bromide and 0.4 mol L⁻¹ 1-ethyl-1-methylpyrrolidone bromide, and the anolyte comprises 2 mol L⁻¹ zinc bromide and 3 mol L⁻¹ potassium chloride.
14. The durable and dendrite-free zinc-bromine flow battery of claim 12, wherein the carbon felt has a geometric area of 4.0 square centimeters and a thickness of 1-5 millimeters.
15. The durable and dendrite-free zinc-bromine flow battery of claim 12, wherein the reaction cell comprises a polytetrafluoroethylene (PTFE) end plate, a PTFE cavity, a PTFE gasket, a PTFE pad, a PTFE tube, a carbon plate, or a titanium foil.
16. The durable and dendrite-free zinc-bromine flow battery of claim 12, wherein the threshold-level electrolyte additive comprises an organophosphorus compound having the following chemical formula (1):
17. The durable and dendrite-free zinc-bromine flow battery of claim 12, wherein the threshold electrolyte additive is selected from the group consisting of the one or more zinc salts described above: hydroxyphosphonic acid-acetic acid (HPAA), acetic acid monohydrate (HEDP), alendronate, and aminotris(methylphosphonic acid).